A Techno-Economic Investigation of a Residential Solar Photovoltaic System at Bandar Universiti, Perak, Malaysia - Badrol Hisham, Muhammad Nadzmi Faez (IRC, 2017)
This report shows theoretical and analytical calculation of Solar Photovoltaic (PV) System in term of its technical and economic feasibility in Bandar Universiti, Seri Iskandar. In this study, PV system is envisioned as a supplement energy that not only help in cutting the cost of today source of electricity, but also can be sell back to Tenaga Nasional Berhad (TNB). Firstly, a PV model was chosen with 3 options of wattages; 30, 60 and 100 Watts. The technical specifications of all 3 wattages are listed including the safety features and material used. Then, a questionnaire survey was conducted which targeted the residents of Bandar Universiti, Seri Iskandar to acquire their electricity usage data and acceptance of PV system application. After the survey, average solar radiation in Bandar Universiti was determined by using a software from National Aeronautics and Space Administration (NASA) website. After the solar radiation data is acquired, a global formula equation was used to determine the approximate energy output generated by PV system. Hence, the Feed-in Tariff (FiT) regulated by Sustainable Energy Development Authority Malaysia (SEDA) is referred to determine the cost of the energy generated to be sold to TNB. There are four main elements to determine the worthiness of the profit gained in PV system application; CAPEX, OPEX, Breakeven and Payback period analysis. Generally, 100 Watts of the model is more viable as it requires less panels and roof space area. Meanwhile, the survey shows that more than 80% of the residents support the effort towards renewable energy because their average electricity bill is determined to be RM108.33 which means the average power usage of the residents is 378.325 kWh per month after referring to the TNB Tariff rate. Besides that, based on NASA website, Bandar Universiti receives a monthly average of 5.22 kWh per day of solar radiation thus energy output is then calculated to be approximately maximum of 2768.548 kWh per month which can further be referred to FiT to be RM1583.05. Next, total CAPEX has a maximum value of RM159,693.40 excluding monthly OPEX of RM644.47